PENGENALAN PRODUK DAN AKAD DALAM PERBANKAN SYARIAH - Chandra Utama (Bina Ekonomi, 2009)
There are so many products that can be offered by Islamic banking.  They must not be done with the ways or procedures that break the Islamic law  (Syaria) for example interest  (riba) which is always done in conventional  banking system.  The application of syaria in the banking operation makes the Islamic Bank different  than conventional one.  In this paper, the products and the transaction (akad)  in Islamic  banking will be described  in simple way. The example of products and akad in the real operating of Islamic Banking also is given to make the explanation more clearly. The Examples are come from Bank Syariah Mandiri Indonesia. It is hope that all simple description about product and akad in Islamic Banking make reader more familiar to the Islamic Banking.